PEA's premium power service: Baseline and risk assessment - Chakphed Madtharad (2018)
This paper addresses the initial stages of developing a premium power offering. First of all, a method of describing the baseline power quality performance is described. Traditional approaches using average performance indices are compared with a statistical approach based on the Weibull distribution. The processing of actual power quality monitoring data from two Provincial Electric Authority (PEA) 22 kV substations is used to compare the two approaches. Secondly, methods of applying the probabilistic techniques to help evaluate the potential for a premium power offering are described. These methods can form the basis of evaluating both supply side and customer side options for addressing PQ performance issues.